Improving Students' Vocabulary on Part of the Body Using Flashcard - Desti (Universitas Islam Al-Ihya Kuningan, 2024)
This research aims to improve the English vocabulary of grade V students of SDN 6 Purwawinangun by using learning media that attracts students' attention, namely flashcard media. This research method used is the classroom action research method. The subjects in this study are grade V students of SDN 6 Purwawinangun Kuningan with a total of 24 students consisting of 13 male students and 11 female students. This classroom action research is carried out in two cycles. In this study, the techniques used for data collection are tests, observation sheets and documentation. The results of the study showed that the use of flash card can improve students' vocabulary in English about parts of the body. This can be proven by looking at the results of observation of teacher activity in the first cycle with a score of 93.75% and in the second cycle it increased to 98.75%. Meanwhile, the results of observation of student activities in the first cycle with a score of 90% and in the second cycle increased to 97.5%. The average score of pre-test was 56.60 and the percentage of student KKM was 45.83% before giving the treatment. Meanwhile, in the first cycle, the average score of post-test was 65.20 with a percentage of KKM is 50%. In the cycle II, the average score of students increased to 76.25 and the percentage of KKM is 79.10%. From the results of pre test post test and observation, it can be conclude that flashcard can improve students' vocabulary in English specially parts of the body.